VAT fraud and reverse charge: empirical evidence from VAT return data - Thiess Buettner; Annalisa Tassi (International Tax and Public Finance, 2023)
In order to stop Value-Added Tax (VAT) fraud, EU member states use the so-called reverse-charge (RC) mechanism, which effectively removes VAT withholding and refunding in business-to-business transactions. Using the German VAT return data, we examine the effects of the introduction of RC and find that requests of input tax refunding decline sharply in the affected industries, supporting the presence of fraud prior to the introduction of RC. Based on our estimates, we quantify the revenue losses from VAT fraud prior to RC implementation in these industries to be around 5% of VAT revenues.
Keywords: H21; H26; 340; Value-added tax; Reverse charge; Tax fraud; Missing-trader fraud